The Effect of Auditor Ethics, Auditor Experience, Audit Fees and Auditor Motivation on Audit Quality - Yeni Kuntari; Anis Chariri; Nurdhiana Nurdhiana (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
This study aimed to determine the effect of auditor ethics, auditor experience, audit fees, and auditor motivation on audit quality of public accounting firm in Semarang. The populations in this study were auditors who work on public accounting firm in Semarang. The total population of public accounting firm in Semarang according to Indonesian Institute of Certified Public Accountants in 2016 was 98 respondents from 14 public accounting firms. Questionnaires were distributed to auditors in all those public accounting firm. This study used purposive sampling judgement with criteria of sample were they have worked and experienced in public accounting firm for one year. A total sample of this study is 30 respondents. Using multiple linier regression analysis the results show that auditor ethics had a significant positive effect on audit quality; auditor experience had a significant positive effect on audit quality; audit fees had a significant positive effect on audit quality; and auditor motivation had a significant positive effect on audit quality. Ethics, experience, fees and motivation of auditor had a significant positive effect on audit quality.